A hybrid model of LCA and emergy for co-benefits assessment associated with waste and by-product reutilization. (1st November 2019) - Liu, Zhe; Liu, Weili; Adams, Michelle; Cote, Raymond P.; Geng, Yong; Chen, Shuilong
Abstract: Life cycle analysis (LCA) and emergy analysis are both considered important methodologies in environmental management. Both methodologies have been applied separately in a variety of situations. Various authors have noted that each method has its limitation but the integration of the two methodologies could have a promising future. In this study, the authors will illustrate a hybrid model by integrating LCA into emergy analysis framework to assess the co-benefits achieved through the application of an eco-industrial strategy in an industrial park. A case study namely Shenyang economic technological development area (SETDA) is undertaken to validate the model. The results show that boiler steam achieves the most co-benefits among the re-utilised resources brought about by the application of the eco-industrial strategy. GHG emissions reduction is only one of the environmental benefits found. From the perspective of unit mass of materials, steel and iron scrap generated the largest co-benefits. Management of the industrial park should investigate initiatives to transfer excess waste heat to potential users through piping systems as well as reutilising steel and iron scrap for productive purposes. The study shows that while each methodology has its own advantages, their weaknesses can be mitigated through a hybrid model.